816 Traveling Waves Reveal a Dynamic Source of Human Focal Seizures and Interictal Spikes. (1st April 2022) - Diamond, Joshua M.; Diamond, Benjamin; Chapeton, Julio; Inati, Sarah K.; Zaghloul, Kareem A.
Abstract : INTRODUCTION: Treatment of patients with drug resistant focal epilepsy relies upon accurate seizure localization. Ictal activity captured in intracranial EEG (iEEG) has traditionally been interpreted to suggest that the underlying cortex is actively seizing. On the other hand, an emerging hypothesis suggests that seizures may in fact emerge from focal regions, which emit discharges that travel over the surface of the cortex as traveling waves. METHODS: 20 patients underwent placement of subdural electrodes for invasive monitoring at the National Instutes of Health, underwent surgical resection for epilepsy, and had at least 1 year of follow-up. Outcomes were measured by the Engel scale. In these patients, we measured the time delay in discharge receipt at adjacent electrodes to compute the location of the seizure source. This algorithm, known as multilateration, has been used for signal source localization with sparsely-spaced sensors for over a century in geophysics, radar, and acoustics, but has not been used in epilepsy until the present. RESULTS: In patients with good outcome, but not in patients with poor outcome, the seizure source tends to localize to the resection territory. The source is a focal, dynamic entity that moves and evolves over the time course of a seizure. Our approach also successfully localizes interictal spikes. We find that interictal spikes emerge from multiple distinct foci in each patient. Seizures either arise from or travel to interictal spike generators. CONCLUSIONS: The seizure source appears to be more focal than has traditionally been conceptualized. This focal source may be localized by measuring the time difference of discharge receipt in intracranial electrodes. Algorithmic source localization, as performed here, may guide pre-surgical planning for drug-resistant epilepsy and may improve outcomes.